1999
DOI: 10.1139/x98-201
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of conifer seed and timing of germination in high-elevation subalpine fir and Engelmann spruce forests of the southern interior of British Columbia

Abstract: Unstratified seed of Engelmann spruce (Picea engelmannii Parry) and subalpine fir (Abies lasiocarpa (Hook.) Nutt.) in nylon mesh bags was placed on various natural and disturbed forest floor seed beds in the Engelmann Spruce - Subalpine Fir Zone in the southern interior of British Columbia in September 1995 and recovered just before snow melt in June 1996. Fifty-two and 86% of the viable spruce and fir seed, respectively, had germinated before snowmelt. Germination under snow may be an adaptation of these high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…Ongoing recruitment of white spruce and balsam fir seedlings most commonly occurs on partially decomposed logs, since elevated logs provide some protection from pathogens (Zhong and van der Kamp 1999), competing herbaceous vegetation, and smothering leaf litter (Lieffers et al 1996b;Simard et al 1998Simard et al , 2003Awada et al 2004). The establishment and growth of advance regeneration is largely related to light and moisture availability (Zasada et al 1992).…”
Section: The Role Of Fire In Stand Initiationmentioning
confidence: 99%
“…Ongoing recruitment of white spruce and balsam fir seedlings most commonly occurs on partially decomposed logs, since elevated logs provide some protection from pathogens (Zhong and van der Kamp 1999), competing herbaceous vegetation, and smothering leaf litter (Lieffers et al 1996b;Simard et al 1998Simard et al , 2003Awada et al 2004). The establishment and growth of advance regeneration is largely related to light and moisture availability (Zasada et al 1992).…”
Section: The Role Of Fire In Stand Initiationmentioning
confidence: 99%
“…The prevalence of rotten wood seedbeds was still clear, but less pronounced, for Abies, in agreement with a study in southern Alberta (Day 1964). Abies is known for its ability to establish also on the forest floor (Smith 1955, Eastham andJull 1999) although pathogenic fungi were demonstrated to cause enhanced first-year mortality of Abies on the undisturbed floor in laboratory trials (Daniel and Schmidt 1972), and of both species in field trials (Zhong and van der Kamp 1999). The low establishment rate of Picea on the forest floor has been attributed to superficial rooting coupled with moisture stress (Noble 1973) under experimental conditions with 50% artificial shade.…”
Section: Microsite Effects On Sapling Occurrencementioning
confidence: 99%
“…These modifications of the soil have been shown to improve establishment and early growth of tree seedlings (Örlander et al 1996), which has been attributed to improvements in soil temperature, moisture, drainage, and aeration conditions (Wilson and Pyatt 1984), faster root penetration and growth (Nadeau and Pluth 1997), and disruption of competing vegetation (Örlander et al 1996). Site preparation also increases the availability of mineralsoil planting spots, which may promote seedling survival by reducing incidence of frosts (Örlander and Nilsson 1999), insect pests (Nordlander et al 2011), and pathogenic fungi (Zhong and van der Kamp 1999). It has also been suggested that site preparation increases nutrient supply for seedlings as a consequence of faster decomposition of the organic matter that becomes mixed with or buried in mineral soil during site preparation (Örlander et al 1998), and several review papers have concluded that site preparation generally causes a decline in soil C stocks (Jandl et al 2007;Hyvönen et al 2007).…”
Section: Introductionmentioning
confidence: 99%